Lyme Neuroborreliosis - J Gordon Millichap (Pediatric Neurology Briefs, 1992)
The clinical and epidemiological features of 187 consecutive patients with neuroborreliosis recognized in Denmark over a 6-year period, 1985-1990, are reported from the Department of Infection-Immunology, Statens Seruminstitut, Copenhagen, Denmark.